The Existence of Borrowing Words in Tourism Articles on the Jawa Pos Online Website in May 2024 - Puspitasari, Prima; Rahayu Puji Haryanti; Abdurrachman Faridi (English Education Journal, 2024)
As language development continues to evolve, especially in a globalized field such as tourism, understanding how borrowing words is integrated into the media in Indonesia is crucial. In line with that, this study investigates the phenomenon of borrowing words and their meaning changes in tourism articles published on the Jawa Pos Online website in May 2024. Hocket's theory (1958) was used to analyze the types of borrowing words, and Baugh's theory (1993) was used to identify the changes in the meaning of the borrowing words. A descriptive qualitative with content analysis method was applied to analyze 173 words found in tourism articles on the Jawa Pos online website in May 2024. The findings show 76 loan words, 63 loan blends, and 92 loan shifts. In the analysis of meaning change, there are 66 extensions, 28 narrowing of the meaning, 10 regeneration of the meaning, and 69 words that did not change the meaning. The findings of this study contribute to journalistic writing, especially in digital media. Also, it contributes to the understanding of Indonesian language development by adapting and incorporating foreign terms.